Response of different sesbania accessions to phosphorus application and fodder quality of S. sesban under acid soil conditions - Berhe, Kahsay; Tothill, J.C.; Mohamed-Saleem, M.A. (1999)
Eleven Sesbania sesban and three S. goetzei accessions were evaluated for dry matter (DM) yield in response to phosphorus (P) application and fodder quality on an acidic Nitosol at Soddo, in the Ethiopian highlands. The soil at this site is known to be P deficient and to have high ability to fix During the first harvest, six months after transplanting, all growth parameters (stem diameter, height and DM yield), showed a highly significant response to P application, except for spread. There were significant (P<0.05) interactions between accessions and P-levels for all parameters. S. sesban accessions performed significantly higher (P<0.05) than all the S. goetzei accessions in the experiment. ILCA accession 15019 (S. sesban) performed best of all accessions. The same was also true for the second harvest (seven months after the first harvest) during which the plants had more woody biomass than during the previous harvest. Some of the newly introduced S. sesban accessions out-yielded the control accession (ILCA 10865). On both harvests, performance of all S. goetzei accessions was very poor. Some differences between accessions of S. sesban were observed with respect to fodder qualities but were generally high and consistent with the expectations for leguminous fodders. Two years after transplanting, all accessions except ILCA 15019 and 13261 were dead, indicating that most of the accessions were not tolerant to soil acidity. Further evaluation of the two accessions on-farm in other similar areas may prove their adaptability and potential for use by the smallholder farmer.